Transnational Pacific Islanders: Implications for Social Work. Issue 2 (31st January 2019) - Godinet, Meripa T; Vakalahi, Halaevalu O; Mokuau, Noreen
Abstract: The Pacific Islander American racial group is smaller in terms of numbers relative to other racial groups and yet one of the fastest-growing in the United States. The complexity of their lives exceeds the implications of such small numbers, yet it reflects the contribution of their transnational ties and relationships in the Pacific and increasing multiple cultural identities as Pacific Islander Americans. Although this identity provides potential opportunities, challenges and struggles in navigating dual cultures and systems is a reality. Thus, commitment to culturally relevant social work practice with transnational Pacific Islander Americans is imperative. Social work practices that acknowledge and integrate indigenous ways of knowing and doing with consideration to the duality of their transnational identities will produce better outcomes. Emphasis on Pacific Islander cultural strengths is fundamental to generating positive health and mental health outcomes as these strengths have sustained Pacific Islanders through experiences of colonization, immigration, and historical trauma. This article discusses the multiple dimensions of the transnational experiences of Pacific Islander Americans and the implications for culturally relevant social work practice, policy, and research.